Imaging by Modification: Numerical Reconstruction of Local Conductivities from Corresponding Power Density Measurements - Capdeboscq, Y; Fehrenbach, J; de Gournay, F; Kavian, O (Society for Industrial and Applied Mathematics, 2009)
We discuss the reconstruction of the impedance from the local power density. This study is motivated by a new imaging principle which allows us to recover interior measurements of the energy density by a noninvasive method. We discuss the theoretical feasibility in two dimensions, and propose numerical algorithms to recover the conductivity in two and three dimensions. The efficiency of this approach is documented by several numerical simulations.